Chasing Light: How Dichromatic LEDs Affect the Elemental Profile of Gongolaria barbata - Melis YILMAZ; İlknur AK (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2023)
This study aims to investigate the influence of three different dichromatic LED light sources and varying photoperiod durations on the mineral content and trace element compositions in cultivated Gongolaria barbata under controlled culture conditions. During the experiment, red-blue (RB), blue-green (BG), red-green (RG) and fluorescent lights were examined at 16:16, 12:12, and 8:16 Light: Dark (L:D) photoperiods, and at 150 μmol photon m-2 s-1 intensity of light in all treatments. The elemental compositions of the thallus samples were analyzed for Mg, Ca, K, Na, P, Zn, Mo, Cu, Mn, Cr, Co, Cd, Fe, and As.. Our results showed that macro element and trace element compositions significantly varied among different experimental groups. Regarding the order of abundance, macroelements were ranked as follows: K > Na > Ca > Mg > P. Meanwhile, trace elements followed this order: As > Zn > Mn > Cr > Co > Cu > Cd > Mo > Fe. Among the experiment groups, the highest value of the macro elements was recorded as 1041.3±22.2 mg kg-1 for K, and the lowest value was 26.61±0.02 mg kg-1 for the P. Among the trace elements, for As, the highest value was recorded as 1339.86±5.27 µg kg -1, and the lowest was determined at 1.93±0.04 mg kg-1 for the Fe. The findings highlight that LED lighting conditions can significantly influence the elemental composition of G. barbata.